Development of E-learning in higher education and future directions - Uhomoibhi, James (2014)
The present paper is based on the work of the ‘Future of E-Learning Group’, a constituent of the EUNIS E-Learning task Force. The group has set up a number of tasks to fulfill its role, one of which, is seeking and disseminating information on the development of e-learning with a view to ensuring the right guide is provided for progress into the future. In our work to date, in this era of globalization, we question the ability of present university systems to respond adequately and appropriately to complex demands of an Information Economy. There’s increasing involvement of private sector in higher education. The effects on future learning on the use of varying tools as well as the design of competency-based performance in e-learning have been reported (Wolrery et al, 2000; Sluijsmans et al, 2006). Several multimedia learning systems are being developed for use as future interactive educational tools (Low et al, 2003). New thinking is required for the new relationships that are being developed between creative subjects and technology when we consider the nature of universities in their present state of existence as public sector institutions. The university of the future can be perceived as a setup, based on international trade in educational services, with universities fulfilling the functions of licensing, quality assurance and cultural custodianship. The pressent paper discusses some of these issues and reports on the future directions of e-learning as they relate to higher education.